Financial Literacy, Inclusion, and Competence in Driving MSME Sustainability: A Mediation–moderation Model of Financial Self-efficacy - Aliah Pratiwi; Nafisah Nurulrahmatiah (Owner : Riset dan Jurnal Akuntansi, 2025)
The purpose of this study was to determine the direct relationship between financial literacy and financial inclusion on financial self-efficacy and MSME performance. The indirect relationship between financial literacy and financial inclusion on MSME performance through financial self-efficacy was also examined, as well as the role of competence as a moderating variable. This study used a quantitative approach by distributing questionnaires. The population in this study was all MSMEs in Bima City and Regency. The sampling technique used was random sampling, which is a random sampling based on a predetermined sample. The total sample size was 225 respondents, with 100 respondents in Bima City and 125 respondents in Bima Regency. The data analysis tool used was Smart PLS. The results of this study indicate that financial literacy and financial inclusion influence financial self-efficacy, and financial self-efficacy also influences the sustainability performance of MSMEs. Similarly, regarding the indirect effect, the results indicate that financial literacy and financial inclusion influence the sustainability performance of MSMEs through financial self-efficacy. Competence moderates the relationship between financial literacy and inclusion on financial self-efficacy, as well as the relationship between financial self-efficacy and the sustainability performance of MSMEs.